2017
DOI: 10.1097/cad.0000000000000498
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-148a promotes apoptosis and suppresses growth of breast cancer cells by targeting B-cell lymphoma 2

Abstract: MicroRNAs (miRNAs) contribute toward tumorigenesis through the modulation of tumor-related genes. MiR-148a has been characterized as a tumor-suppressing miRNA and its downregulation has been reported in tumors of a variety of cancers. However, the functional role of miR-148a in breast cancer is not yet fully understood. Using both in-vitro and in-vivo models, we confirmed that miR-148a acts to inhibit the proliferation of breast cancer cells. Through the use of bioinformatic approaches in miRNA target predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 36 publications
2
22
0
Order By: Relevance
“… 8 For example, miR-198 inhibited cell proliferation and migration and promoted cell adhesion in aggressive breast cancer by targeting CUB domain-containing protein 1 (CDCP1); 9 miR-340 suppressed the migration, invasion, and metastasis of breast cancer cells through modulating Wnt/β-catenin signaling pathway; 10 miR-148a accelerated cell apoptosis and restricted growth of breast cancer cells via regulating B-cell lymphoma 2 (Bcl-2). 11 Therefore, miRNAs are regarded as reliable prognostic markers, promising therapeutic targets, or new drugs, which would be essential in the prevention and treatment of breast cancer. 12 …”
Section: Introductionmentioning
confidence: 99%
“… 8 For example, miR-198 inhibited cell proliferation and migration and promoted cell adhesion in aggressive breast cancer by targeting CUB domain-containing protein 1 (CDCP1); 9 miR-340 suppressed the migration, invasion, and metastasis of breast cancer cells through modulating Wnt/β-catenin signaling pathway; 10 miR-148a accelerated cell apoptosis and restricted growth of breast cancer cells via regulating B-cell lymphoma 2 (Bcl-2). 11 Therefore, miRNAs are regarded as reliable prognostic markers, promising therapeutic targets, or new drugs, which would be essential in the prevention and treatment of breast cancer. 12 …”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that miR-148a regulates ERα expression through DNMT1-mediated DNA methylation in BC cells [366]. In contrast, it has been reported that miR-148a targets B-cell lymphoma 2 (BCL-2), which is frequently upregulated in BC [367]. Nuclear receptor NR4A1 (Nur77) promotes BC invasion and metastasis by activating TGF-β signaling [368,369].…”
Section: Breast Cancermentioning
confidence: 99%
“…Furthermore, increasing miRNAs has been reported to play an important role in colorectal cancer, such as miR-144, miR-495, miR-590, miR-6803 (811). miR-148a has been reported to be downregulated in many kinds of tumors including breast cancer, renal cell carcinoma and endometrial cancer (1214). According to Li et al (12), miR-148a promotes apoptosis and inhibits growth of breast cancer.…”
Section: Introductionmentioning
confidence: 99%